The Influence of Principal Intructional Leadership, School Culture and Teacher Commitment on Lesson Planning Quality in Senior High School - Ekawati, Herlina; Egar, Ngasbun; Ginting, Rosalina Br (Electronic Journal of Education, Social Economics and Technology, 2024)
The quality of lesson planning in public senior high schools in Blora Regency remains low due to suboptimal principal instructional leadership, inadequate school culture, and low teacher commitment in preparing high-quality lesson plans. This study aims to analyze the influence of principal instructional leadership, school culture, and teacher commitment on lesson planning quality A quantitative approach with an ex post facto method was used. The sample consisted of 200 public senior high school teachers, selected through random sampling. Data were collected using validated and reliable questionnaires. Multiple linear regression was applied for data analysis. The findings indicate that principal instructional leadership has a positive and significant effect on lesson planning quality (r = 0.810, contribution 65.7%). School culture significantly influences lesson planning quality (r = 0.800, contribution 64%), while teacher commitment also has a significant impact (r = 0.806, contribution 65%). Combined, these three variables contribute 72.6% to lesson planning quality.These results highlight the importance of strengthening principal instructional leadership, fostering a positive school culture, and enhancing teacher commitment to improve the quality of lesson planning in school.